Method for synthesizing mesitylene by gas-phase non-hydroisomerization of unsym-trimethylbenzene

By using EWT structured molecular sieve catalysts with ultra-large pores, the problem of easy catalyst deactivation was solved, and efficient production of mesitylene was achieved, meeting the needs of industrial production.

CN120864945APending Publication Date: 2025-10-31CHINA PETROLEUM & CHEMICAL CORP +1

Patent Information

Application Number
CN202410542471.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-04-30
Publication Date
2025-10-31

AI Technical Summary

Technical Problem

Existing catalysts in the production of mesitylene suffer from short catalyst life and easy deactivation, especially under non-hydrogen-dependent gas phase conditions, making it difficult to maintain high selectivity and high conversion rate. Furthermore, industrial applications are subject to high energy consumption and demanding equipment requirements.

Method used

EWT structured molecular sieves with ultra-large pore structure were used as catalysts. EWT structured molecular sieves were prepared through two-stage hydrothermal crystallization and ion exchange steps and used for the gas-phase non-hydroisomerization reaction of pseudotrimethylbenzene. This improved the pore volume and acidity distribution of the catalyst and enhanced the catalytic effect.

Benefits of technology

It improves the conversion rate of pseudotrimethylbenzene and the selectivity and mass yield of mesitylene, extends the service life of the catalyst, slows down the carbon deposition of heavy components, and meets the continuous needs of large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120864945A_ABST
    Figure CN120864945A_ABST
Patent Text Reader

Abstract

The invention relates to a method for synthesizing mesitylene by gas-phase non-hydroisomerization of unsym-trimethylbenzene, which comprises the following step of: contacting the unsym-trimethylbenzene with a catalyst under a gas-phase non-hydroisomerization reaction condition in the presence of the catalyst, wherein the catalyst is an EWT structure molecular sieve, the total pore volume of the EWT structure molecular sieve is 0.20-0.51 cm < 3 >. G <-1 >, and the mesoporous volume is 0.11-0.37 cm < 3 >. G <-1 >. According to the method disclosed by the invention, the EWT structure molecular sieve with an ultra-large pore channel structure is adopted as the catalyst, and when the catalyst is used for synthesizing mesitylene through unsym-trimethylbenzene gas-phase non-hydroisomerization, the distribution conditions of raw materials and products are improved, the conversion rate of unsym-trimethylbenzene and the selectivity and the mass yield of mesitylene are improved, heavy component carbon deposition is slowed down, and the yield of mesitylene is improved. The service life of the catalyst is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to the field of petrochemical technology, specifically to a method for synthesizing mesitylene by gas-phase non-hydroisomerization of pseudotrimethylbenzene. Background Technology

[0002] The production methods of mesitylene include separation and synthesis. Because its boiling point is similar to that of o-toluene, it is difficult to purify using ordinary distillation. Cryogenic crystallization, hydrogen fluoride-boron fluoride extraction, and 3,5-dinitrobenzoic acid complexation are difficult to apply industrially due to high energy consumption and complex reaction processes. Currently, the more mature and promising chemical synthesis methods reported in domestic and international research mainly include: isomerization of mesitylene, acetone condensation, and mixed xylene isomerization.

[0003] Among them, isomerization of pseudotrimethylbenzene is one of the main methods for producing mesitylene. In existing technologies, Tang Yi et al. synthesized a loosely morphological MTW-type molecular sieve by changing the H2O / SiO2 ratio. When this molecular sieve was used in pseudotrimethylbenzene isomerization studies, the pseudotrimethylbenzene conversion rate was 64-36% within 4 hours, and the selectivity of mesitylene in trimethylbenzene was 73-70%. However, the catalyst rapidly deactivated within the first 40 minutes, and then the pseudotrimethylbenzene conversion rate stabilized at 36%. Li Xiaofeng et al. used seed solution-assisted template-free synthesis of different... ZSM-5 molecular sieves with a silica-to-alumina ratio are used for the hydroisomerization of pseudotrimethylbenzene in the gas phase, achieving a pseudotrimethylbenzene conversion of 10–32% and a mesitylene selectivity of 50–63%. CN116786158A discloses a composite molecular sieve catalyst formed by hierarchical H-Beta and MOR molecular sieves, with the addition of rare earth metals, Group VIII, Group IIIB, and Group IVB elements for the hydroisomerization of pseudotrimethylbenzene in the gas phase, achieving a pseudotrimethylbenzene conversion of 40–50% and a mesitylene selectivity of 46–60%. All of the above molecular sieve catalysts are mesoporous molecular sieves. Due to their narrow pore structure, molecular sieves are characterized by short catalyst lifetimes and easy deactivation.

[0004] Because mesitylene has a large molecular diameter and limited diffusion, continuous gas-phase non-hydrogen-exposed reactions often lead to rapid catalyst deactivation. On the one hand, it is necessary to add metal components to the catalyst to inhibit coking and conduct gas-phase isomerization under hydrogen-exposed conditions, or liquid-phase isomerization under pressure. On the other hand, it is necessary to select molecular sieve catalysts with large pore structures and good diffusion performance to maintain product selectivity and ensure catalyst lifetime. However, hydrogen-exposed operating conditions are harsh, equipment requirements are high, and energy consumption is high; liquid-phase reactions require high pressures, resulting in poor production continuity and making them unsuitable for large-scale industrial production. Summary of the Invention

[0005] The purpose of this disclosure is to provide a method for the gas-phase non-hydroisomerization synthesis of mesitylene from pseudotrimethylbenzene. This method uses an EWT molecular sieve with an ultra-large pore structure as a catalyst. When used for the gas-phase non-hydroisomerization synthesis of mesitylene from pseudotrimethylbenzene, it is beneficial to improve the distribution of raw materials and products, increase the conversion rate of pseudotrimethylbenzene, the selectivity and mass yield of mesitylene, and slow down the carbon deposition of heavy components, thus extending the service life of the catalyst.

[0006] To achieve the above objectives, this disclosure provides a method for synthesizing mesitylene via a gas-phase non-hydroisomerization reaction of pseudotrimethylbenzene. The method includes: contacting pseudotrimethylbenzene with a catalyst under gas-phase non-hydroisomerization reaction conditions and in the presence of a catalyst; wherein the catalyst is an EWT-structured molecular sieve, and the total pore volume of the EWT-structured molecular sieve is 0.20–0.51 cm³. 3 ·g -1 The mesopore volume is 0.11–0.37 cm³. 3 ·g -1 .

[0007] Optionally, the conditions for the gas-phase non-hydroisomerization reaction include: contacting the catalyst with p-xylene under a nitrogen atmosphere, wherein the nitrogen flow rate is 5–50 mL / min, preferably 10–30 mL / min; the contact temperature is 240–400 °C, preferably 280–360 °C; the contact time is 10–60 h, preferably 20–45 h; and the pressure is 0.1–1.2 MPa, preferably 0.1–0.5 MPa. Preferably, the reaction is carried out in a fixed-bed reactor, and the mass hourly space velocity (WHSV) of p-xylene is 0.5–1.0 h⁻¹. -1 .

[0008] Optionally, the total pore volume of the EWT structured molecular sieve is 0.28–0.46 cm³. 3 ·g -1 The mesopore volume is 0.15–0.35 cm³. 3 ·g -1 The total specific surface area is 500-600 m². 2 ·g -1 Preferably, it is 520-550m 2 g -1 .

[0009] Optionally, the amount of moderately strong acid in the EWT structured molecular sieve, as determined by the NH3-TPD method, accounts for 40-65% of the total acid amount, preferably 60-65%; the ratio of Brønsted acid to Lewis acid, as determined by pyridine adsorption infrared spectroscopy at 200℃, is 0.5-2, preferably 1-2; the ratio of Brønsted acid to Lewis acid, as determined by pyridine adsorption infrared spectroscopy at 350℃, is 0.1-0.4, preferably 0.15-0.4; preferably, the total acid amount of the EWT structured molecular sieve, as determined by the NH3-TPD method, is 420-600 μmol / g, preferably 550-600 μmol / g.

[0010] Optionally, the molar ratio of silicon (calculated as SiO2) to aluminum (calculated as Al2O3) in the EWT structured molecular sieve is 60–120, preferably 60–90; the EWT structured molecular sieve has a layered structure and is an H-EWT molecular sieve.

[0011] Optionally, the method further includes preparing the EWT structured molecular sieve using the following steps:

[0012] (1) A silicon source, an aluminum source, an alkali source, a structure-directing agent, water, and an optional mineralizer are mixed to obtain a first mixture; the first mixture is subjected to a first stage of hydrothermal crystallization and a second stage of hydrothermal crystallization to obtain a gel molecular sieve; wherein the temperature of the first stage of hydrothermal crystallization is lower than the temperature of the second stage of hydrothermal crystallization.

[0013] (2) The gel molecular sieve is flocculated and mixed with the first ammonium salt solution, and the resulting second mixture is subjected to first drying and first calcination to obtain a solid molecular sieve;

[0014] (3) The solid molecular sieve is brought into contact with the second ammonium salt solution for ion exchange, and then subjected to second drying and second calcination.

[0015] Optionally, in step (1), the silicon source is SiO2, the aluminum source is Al2O3, the alkali source is alkali metal oxide M2O, and the structure directing agent is SDR. In the first mixture, the molar ratio of SiO2 to Al2O3 is 60–180, preferably 60–120; the molar ratio of M2O to SiO2 is 0.01–0.2, preferably 0.04–0.18; the molar ratio of SDR to SiO2 is 0.06–0.18, preferably 0.10–0.16; and the molar ratio of water to SiO2 is 8–20, preferably… 9–15; the molar ratio of mineralizer to SiO2 is 0–0.1, preferably 0–0.05; the absolute value of the temperature difference between the first stage of hydrothermal crystallization and the second stage of hydrothermal crystallization is 15–55℃, preferably 20–40℃; more preferably, the temperature of the first stage of hydrothermal crystallization is 100–160℃, preferably 120–140℃; the time is 12–48h, preferably 24–48h; the temperature of the second stage of hydrothermal crystallization is 150–180℃, preferably 160–180℃; the time is 96–132h, preferably 96–120h.

[0016] Optionally, in step (1), the silicon source is selected from one or more of solid silica gel, silica sol, tetraethyl orthosilicate, and silica, preferably solid silica gel; the aluminum source is selected from one or more of sodium aluminate, aluminum trichloride, aluminum sulfate, and aluminum sol, preferably sodium aluminate; the alkali source is selected from one or more of sodium hydroxide, potassium hydroxide, sodium oxide, and potassium oxide, preferably sodium hydroxide; the structure directing agent is selected from at least one having the structure shown in formula (1):

[0017]

[0018] R1 to R4 are each independently selected from alkyl groups having 1 to 4 carbon atoms. Preferably, R1 to R4 are each independently selected from one or more of methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, and tert-butyl, preferably methyl or ethyl; m is 2 or 3; n is any integer from 1 to 10; X - This includes hydroxide ions or halide anions.

[0019] Optionally, in step (2), the weight ratio of the gel molecular sieve to the first ammonium salt solution is 1:(10-50), preferably 1:(10-30); the temperature of the first drying is 80-150℃, preferably 100-120℃; the time is 8-12h, preferably 8-10h; the temperature of the first calcination is 400-600℃, preferably 450-550℃; the time is 2-6h, preferably 3-5h; the concentration of the first ammonium salt solution is 10-30% by weight, and the first ammonium salt solution is selected from one or more of ammonium chloride solution, ammonium nitrate solution and ammonium sulfate solution.

[0020] Optionally, in step (3), the weight ratio of the solid molecular sieve to the second ammonium salt solution is 1:(10-40), preferably 1:(20-30); the ion exchange temperature is 60-100℃, preferably 65-80℃; the time is 2-8h, preferably 4-8h; the second drying temperature is 80-150℃, preferably 80-120℃; the time is 8-12h, preferably 8-10h; the second calcination temperature is 400-600℃, preferably 450-550℃; the time is 2-6h, preferably 3-5h; the concentration of the second ammonium salt solution is 10-30% by weight, and the second ammonium salt solution is selected from one or more of ammonium chloride solution, ammonium nitrate solution, and ammonium sulfate solution.

[0021] This disclosure provides a method for synthesizing mesitylene via gas-phase non-hydroisomerization of pseudotrimethylbenzene using the above technical solution. This method employs an EWT-structured molecular sieve with an ultra-large pore structure as a catalyst. Compared to mesoporous molecular sieves such as MOR, the EWT-structured molecular sieve has a three-dimensional pore system composed of 21MR and 10MR pores, and possesses suitable total pore volume and mesopore volume. When used for the gas-phase non-hydroisomerization of pseudotrimethylbenzene to synthesize mesitylene, it is beneficial for improving the distribution of raw materials and products, increasing the isomerization reaction rate of pseudotrimethylbenzene, and improving the diffusion rate of the product mesitylene. This results in higher pseudotrimethylbenzene conversion, mesitylene selectivity, and mass yield, while also mitigating carbon deposition of heavy components, improving reaction stability, and extending catalyst lifespan. Specifically, the pseudotrimethylbenzene conversion is 45–50%, the mesitylene selectivity is 50–65%, and the mesitylene yield is 17–35%. Even after 90 hours of continuous reaction, the mesitylene yield remains high, above 20%, indicating that the catalyst's stability time exceeds 90 hours.

[0022] Other features and advantages of this disclosure will be described in detail in the following detailed description section. Attached Figure Description

[0023] The accompanying drawings are provided to further illustrate the present disclosure and form part of the specification. They are used together with the following detailed description to explain the present disclosure, but do not constitute a limitation thereof. In the drawings:

[0024] Figure 1 This is the XRD pattern of catalyst 1 prepared in Example 1 of this disclosure;

[0025] Figure 2 This is a SEM image of catalyst 1 prepared in Example 1 of this disclosure;

[0026] Figure 3 This is a nitrogen adsorption-desorption isotherm curve of catalyst 1 prepared in Example 1 of this disclosure and comparative catalyst 3 prepared in Comparative Example 3.

[0027] Figure 4 This is a high-temperature aerobic weight loss curve of catalyst 1 prepared in Example 1 and comparative catalyst 3 prepared in Comparative Example 3 after 90 h of catalytic gas-phase non-hydroisomerization reaction of pseudotrimethylbenzene. Detailed Implementation

[0028] The specific embodiments of this disclosure will be described in detail below with reference to the accompanying drawings. It should be understood that the specific embodiments described herein are for illustration and explanation only and are not intended to limit this disclosure.

[0029] This disclosure provides a method for synthesizing mesitylene via gas-phase non-hydroisomerization of pseudotrimethylbenzene. The method includes contacting pseudotrimethylbenzene with a catalyst under gas-phase non-hydroisomerization reaction conditions and in the presence of a catalyst; wherein the catalyst is an EWT-structured molecular sieve with a total pore volume of 0.20–0.51 cm³. 3 ·g -1 The mesopore volume is 0.11–0.37 cm³. 3 ·g -1 .

[0030] The method disclosed herein uses an EWT-structured molecular sieve with a relatively large pore structure as a catalyst. Compared to mesoporous molecular sieves such as MOR molecular sieves, this EWT-structured molecular sieve is a three-dimensional pore system composed of 21MR and 10MR pores, and has suitable total pore volume and mesopore volume. When used for the gas-phase non-hydroisomerization synthesis of mesitylene from pseudotrimethylbenzene, it is beneficial to improve the distribution of raw materials and products, increase the isomerization reaction rate of pseudotrimethylbenzene, and increase the diffusion rate of the product mesitylene. This results in higher pseudotrimethylbenzene conversion, mesitylene selectivity, and mass yield, while also slowing down carbon deposition of heavy components, improving reaction stability, and extending the catalyst's lifespan. Even after 90 hours of continuous reaction, the catalyst still maintains a high mesitylene yield, which remains above 20% without significant decline.

[0031] In one embodiment of this disclosure, the conditions for the gas-phase non-hydroisomerization reaction include: contacting the catalyst with pseudotrimethylbenzene under a nitrogen atmosphere, wherein the nitrogen flow rate is 5–50 mL / min, preferably 10–30 mL / min; the contact temperature is 240–400 °C, preferably 280–360 °C; the contact time is 10–60 h, preferably 20–45 h; and the pressure is 0.1–1.2 MPa, preferably 0.1–0.5 MPa. Preferably, the reaction is carried out in a fixed-bed reactor, and the mass hourly space velocity (WHSV) of the pseudotrimethylbenzene is 0.5–1.0 h⁻¹. -1 In the above embodiments, by selecting preferred gas-phase non-hydroisomerization reaction conditions, it is beneficial for pseudotrimethylbenzene to fully contact with the catalyst, thereby further improving the conversion rate of pseudotrimethylbenzene and the product selectivity.

[0032] In one embodiment of this disclosure, the total pore volume of the EWT structured molecular sieve is 0.28–0.46 cm³. 3 ·g -1 The mesopore volume is 0.15–0.35 cm³. 3 ·g -1 The total specific surface area is 500-600 m². 2 ·g -1 Preferably, it is 520-550m 2 g -1 In the above embodiments, by selecting EWT structure molecular sieves with preferred pore structure and external specific surface area, it is beneficial to further improve the isomerization reaction rate and the diffusion rate of the product.

[0033] In one embodiment of this disclosure, the EWT structured molecular sieve, as measured by the NH3-TPD method, contains 40-65% medium-strong acid, preferably 60-65% of the total acid content; the ratio of Brønsted acid (B) to Lewis acid (L) content, as measured by pyridine adsorption infrared spectroscopy at 200°C, is 0.5-2, preferably 1-2; and the ratio of B to L acid content, as measured by pyridine adsorption infrared spectroscopy at 350°C, is 0.1-0.4, preferably 0.15-0.4. In a preferred embodiment, the total acid content of the EWT structured molecular sieve, as measured by the NH3-TPD method, is 420-600 μmol / g, preferably 550-600 μmol / g. In the above embodiments, the EWT structured molecular sieve has suitable acid content and acid strength, and a suitable B / L value, which is beneficial for improving the conversion rate of pseudotrimethylbenzene and the product selectivity.

[0034] In this disclosure, a weak acid refers to an acid with a desorption temperature of 100–250 °C in NH3-TPD (temperature programmed desorption), a moderately strong acid refers to an acid with a desorption temperature of 250–500 °C in NH3-TPD (temperature programmed desorption), a strong acid refers to an acid with a desorption temperature of 500–600 °C in NH3-TPD (temperature programmed desorption), and a total acid refers to the sum of weak acids, moderately strong acids, and strong acids.

[0035] In one embodiment of this disclosure, the molar ratio of silicon (calculated as SiO2) to aluminum (calculated as Al2O3) in the EWT structured molecular sieve is 60–120, preferably 60–90; the EWT structured molecular sieve has a layered structure and is an H-EWT molecular sieve. In the above embodiment, the EWT structured molecular sieve has a suitable silicon-to-aluminum ratio.

[0036] In one embodiment of this disclosure, the method further includes preparing the EWT structured molecular sieve using the following steps:

[0037] (1) A silicon source, an aluminum source, an alkali source, a structure-directing agent, water, and an optional mineralizer are mixed to obtain a first mixture; the first mixture is subjected to a first stage of hydrothermal crystallization and a second stage of hydrothermal crystallization to obtain a gel molecular sieve; wherein the temperature of the first stage of hydrothermal crystallization is lower than the temperature of the second stage of hydrothermal crystallization.

[0038] (2) The gel molecular sieve is flocculated and mixed with the first ammonium salt solution, and the resulting second mixture is subjected to first drying and first calcination to obtain a solid molecular sieve;

[0039] (3) The solid molecular sieve is brought into contact with the second ammonium salt solution for ion exchange, and then subjected to second drying and second calcination.

[0040] In the above embodiments, a two-stage hydrothermal crystallization method is used. After solid-liquid separation, drying and calcination, ion exchange, and drying and calcination again, an EWT structure molecular sieve with an ultra-large pore structure is prepared. This molecular sieve has a three-dimensional pore system composed of 21MR and 10MR pores, and has suitable total pore volume and mesopore volume. When it is used for the gas-phase non-hydroisomerization synthesis of mesitylene from pseudotrimethylbenzene, it is beneficial to improve the distribution of raw materials and products, and obtain higher pseudotrimethylbenzene conversion, mesitylene selectivity and mass yield.

[0041] In one embodiment of this disclosure, in step (1), the silicon source is SiO2, the aluminum source is Al2O3, the alkali source is alkali metal oxide M2O, and the structure directing agent is SDR. The molar ratio of SiO2 to Al2O3 in the first mixture is 60–180, preferably 60–120; the molar ratio of M2O to SiO2 is 0.01–0.2, preferably 0.04–0.18; the molar ratio of SDR to SiO2 is 0.06–0.18, preferably 0.10–0.16; and the molar ratio of water to SiO2 is 8–2. The molar ratio of mineralizer to SiO2 is 0 to 0.1, preferably 0 to 0.05; the absolute value of the temperature difference between the first stage of hydrothermal crystallization and the second stage of hydrothermal crystallization is 15 to 55°C, preferably 20 to 40°C; more preferably, the temperature of the first stage of hydrothermal crystallization is 100 to 160°C, preferably 120 to 140°C; the time is 12 to 48 hours, preferably 24 to 48 hours; the temperature of the second stage of hydrothermal crystallization is 150 to 180°C, preferably 160 to 180°C; the time is 96 to 132 hours, preferably 96 to 120 hours.

[0042] In one embodiment of this disclosure, in step (1), the silicon source is selected from one or more of solid silica gel, silica sol, tetraethyl orthosilicate, and silica, preferably solid silica gel; the aluminum source is selected from one or more of sodium aluminate, aluminum trichloride, aluminum sulfate, and aluminum sol, preferably sodium aluminate; the alkali source is selected from one or more of sodium hydroxide, potassium hydroxide, sodium oxide, and potassium oxide, preferably sodium hydroxide; the structure directing agent is selected from at least one having the structure shown in formula (1):

[0043]

[0044] R1 to R4 are each independently selected from alkyl groups having 1 to 4 carbon atoms. Preferably, R1 to R4 are each independently selected from one or more of methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, and tert-butyl, preferably methyl or ethyl; m is 2 or 3; n is any integer from 1 to 10; X - This includes hydroxide ions or halide anions.

[0045] In one embodiment of this disclosure, in step (2), the weight ratio of the gel molecular sieve to the first ammonium salt solution is 1:(10-50), preferably 1:(10-30); the first drying temperature is 80-150℃, preferably 100-120℃; the time is 8-12h, preferably 8-10h; the first calcination temperature is 400-600℃, preferably 450-550℃; the time is 2-6h, preferably 3-5h; the concentration of the first ammonium salt solution is 10-30% by weight, and the first ammonium salt solution is selected from one or more of ammonium chloride solution, ammonium nitrate solution, and ammonium sulfate solution. In the above embodiment, using the first ammonium salt solution to flocculate and mix the gel molecular sieve is beneficial for solid-liquid separation and charge balance of the gel molecular sieve, and promotes the subsequent ion exchange.

[0046] In one embodiment of this disclosure, in step (3), the weight ratio of the solid molecular sieve to the second ammonium salt solution is 1:(10-40), preferably 1:(20-30); the ion exchange temperature is 60-100℃, preferably 65-80℃; the time is 2-8h, preferably 4-8h; the second drying temperature is 80-150℃, preferably 80-120℃; the time is 8-12h, preferably 8-10h; the second calcination temperature is 400-600℃, preferably 450-550℃; the time is 2-6h, preferably 3-5h; the concentration of the second ammonium salt solution is 10-30% by weight, and the second ammonium salt solution is selected from one or more of ammonium chloride solution, ammonium nitrate solution, and ammonium sulfate solution. In the above embodiment, using the second ammonium salt solution for ion exchange of the solid molecular sieve is beneficial for forming a hydrogen-form molecular sieve.

[0047] The present disclosure will be further illustrated by the following examples, but the present disclosure is not limited thereto.

[0048] In the embodiments and comparative examples of this disclosure, a Quanta 200F scanning electron microscope (SEM) from FEI Corporation was used for microscopic morphology analysis, with the working voltage of the SEM being 20 kV; the average particle size of the catalyst was measured using a Japan Hitachi S-4800type instrument.

[0049] The chemical composition of the molecular sieve was determined using a Rigaku Electric Co., Ltd. 3013 X-ray fluorescence spectrometer. The silicon-to-aluminum ratio of the molecular sieve was calculated. The tungsten target was used, the excitation voltage was 40 kV, and the excitation current was 50 mA.

[0050] Specific surface area and pore volume were determined using an AS-3 or AS-6 static nitrogen adsorption analyzer manufactured by Quantachrome Instruments. The specific method was as follows: the sample was placed in the sample processing system, and a vacuum was drawn to 1.33 × 10⁻⁶ at 300°C. -2 The sample was purified by holding it at a pressure of 4 h under pressure and temperature. At a liquid nitrogen temperature of -196℃, the adsorption and desorption of nitrogen on the purified sample under different specific pressures P / P0 were tested to obtain N2 adsorption-desorption isotherms. The specific surface area of ​​the sample was calculated using the BET method, and the mesopore volume of the sample was calculated using the t-plot method. The adsorption amount at specific pressures P / P0 = 0.98 or lower was taken as the total pore volume of the sample.

[0051] The acid content of moderately strong acids and the total acid content were measured using the NH3-TPD method. The determination was performed using an Autochem II 2920 temperature-programmed desorption instrument from Micron Technology, USA. The specific method was as follows: 0.2 g of the sample was weighed and placed in a sample tube, which was then placed in a thermal conductivity cell furnace. He gas was used as the carrier gas (50 mL / min), and the temperature was increased to 600 °C at a rate of 20 °C / min. The sample was purged for 60 min to remove impurities adsorbed on the catalyst surface. The temperature was then reduced to 100 °C and held for 30 min. An NH3-He mixture (10.02% NH3 + 89.98% He) was then used for adsorption for 30 min. He gas was then used to purge for another 90 min until the baseline stabilized, allowing for the desorption of physically adsorbed ammonia. The temperature was increased to 600 °C at a rate of 10 °C / min and held for 30 min. Desorption was then completed. A TCD detector was used to detect changes in gas composition, and the instrument automatically integrated the results to obtain the total acid content.

[0052] The acid content of Brønsted (B) and Lewis (L) acids was measured using a pyridine adsorption infrared spectroscopy method with a Bruker Vertex 70 instrument. The specific method involved pressing the catalyst to a concentration of 10 mg / cm³. 2 Thin slices were placed in an infrared cell with a CaF2 window. The cell was first evacuated to 400°C, then cooled to 150°C to adsorb pyridine for 15 minutes, followed by evacuation for 1 hour. The cell was then cooled to room temperature, and spectra were collected. The amounts of Brønsted acid and Lewis acid were calculated. See Applied Catalysis A:General, 294, 2005: 92.

[0053] The conversion rate of pseudotrimethylbenzene and the selectivity of mesitylene were calculated using the gas chromatography peak area normalization method. The specific testing method was as follows: nitrogen was used as the carrier gas; an FID detector was used; the column temperature was 80℃; the injector temperature was 260℃; and the detector temperature was 250℃. The programmed temperature rise was 0℃ initially, held for 0 min at a rate of 3℃ / min, and reached a final temperature of 50℃ with a holding time of 20 min. The injection volume was 0.2 μL.

[0054] High-temperature thermogravimetric analysis of the molecular sieve catalyst after reaction was performed using a Netzsch STA409CD analyzer. The temperature was increased from 30°C to 1200°C at a rate of 10°C / min in an air atmosphere of 100 ml / min to detect the rate of weight loss of carbon deposits. See Fuel 318(2022)123696.

[0055] Preparation Example 1

[0056] (1) 6g of solid silica gel (silicon source, 93.2% by mass as SiO2, the same below), 1.908g of sodium aluminate (aluminum source, 8.3% by mass as Al2O3, 15.8% by mass as NaOH, the same below), and 13.872g of structure directing agent TDUH (molecular formula is C 13 H 30 N2(OH)2, MW = 248, structural formula is: SDR (represented by a mass fraction of 25%, the same below) and 4.452 g of water were added to the Teflon liner in a liquid-to-solid order and mixed thoroughly to prepare the first mixture. The molar ratios of the components in the first mixture were: SiO2 / Al2O3 = 60, Na2O / SiO2 = 0.04, SDR / SiO2 = 0.15, and H2O / SiO2 = 10.

[0057] The first mixture was placed in a high-pressure reactor with a volume of 45 ml and subjected to two-stage hydrothermal crystallization in a homogeneous reactor. The temperature of the first stage of hydrothermal crystallization was 120 °C and the time was 24 h. The temperature of the second stage of hydrothermal crystallization was 160 °C and the time was 120 h, resulting in a gel molecular sieve. The absolute value of the temperature difference between the first stage of hydrothermal crystallization and the second stage of hydrothermal crystallization was 40 °C.

[0058] (2) The above-mentioned gel molecular sieve was mixed with a 30% ammonium chloride solution (first ammonium salt solution) by flocculation. The weight ratio of gel molecular sieve to ammonium chloride solution was 1:20. The filtered solid was placed in a drying oven at 110℃ for the first drying for 8 hours. After grinding, it was placed in a muffle furnace at 550℃ for the first calcination for 4 hours to remove the structure guiding agent and obtain solid molecular sieve.

[0059] (3) Solid molecular sieves were mixed with a 10% ammonium chloride solution (second ammonium salt solution) for ion exchange. The weight ratio of solid molecular sieves to ammonium chloride solution was 1:20. The ion exchange was performed three times at a temperature of 80℃ for 4 hours. After three centrifugations until the pH value was neutral, the centrifugation speed was 5000 r / min and the time was 15 min, resulting in an ammonium-type molecular sieve. The ammonium-type molecular sieve was placed in a drying oven at 120℃ for a second drying for 10 hours. After grinding, it was placed in a muffle furnace at 550℃ for a second calcination for 3 hours to obtain H-EWT molecular sieves, i.e., EWT structured molecular sieves. The molecular sieves were pressed into sheets under a pressure of 20 MPa, and particles of 20-40 mesh (i.e., average particle size of 0.63-0.85 mm) were screened as catalyst 1, denoted as E-1. Its physicochemical properties are shown in Tables 1-2.

[0060] The XRD pattern of the prepared catalyst E-1 is as follows: Figure 1 As shown, Figure 1 The XRD pattern of E-1 shows peaks around 2θ = 5.1°, 8.2°, and 8.9°, indicating that E-1 is an EWT structure molecular sieve; the SEM image is shown below. Figure 2 As shown, Figure 2 It can be seen that E-1 has a lamellar morphology and a large specific surface area; the nitrogen isotherm curve is shown in the figure. Figure 3 As shown, Figure 3 It can be seen that E-1 has a large number of mesoporous structures.

[0061] Preparation Example 2

[0062] The preparation method was the same as in Example 1, except that the molar ratios of the components in the first mixture were: SiO2 / Al2O3 = 90, Na2O / SiO2 = 0.04, SDR / SiO2 = 0.15, and H2O / SiO2 = 10. Specifically, 6g of solid silica gel (silicon source, calculated as SiO2), 1.272g of sodium aluminate (aluminum source, calculated as Al2O3), 0.101g of sodium hydroxide (alkali source, 96% by mass as alkali metal oxide M2O, the same below), 13.872g of structure directing agent (TDUH, represented as SDR), and 4.958g of water were added to the Teflon liner in a liquid-to-solid order and mixed thoroughly to prepare the first mixture. Catalyst 2, denoted as E-2, was finally obtained, and its physicochemical properties are shown in Tables 1-2.

[0063] The XRD pattern of E-2 shows peaks near 2θ = 5.1°, 8.2°, and 8.9°, indicating that catalyst E-2 is an EWT structure molecular sieve.

[0064] Preparation Example 3

[0065] The preparation method was the same as in Example 1, except that the molar ratios of the components in the first mixture were: SiO2 / Al2O3 = 120, Na2O / SiO2 = 0.04, SDR / SiO2 = 0.15, and H2O / SiO2 = 10. Specifically, 6g of solid silica gel (silicon source, calculated as SiO2), 0.954g of sodium aluminate (aluminum source, calculated as Al2O3), 0.154g of sodium hydroxide (alkali source, calculated as alkali metal oxide M2O), 13.872g of structure directing agent (TDUH, represented as SDR), and 5.211g of water were added to the Teflon liner in a liquid-to-solid order and mixed thoroughly to prepare the first mixture. The final catalyst was 3, denoted as E-3. Its physicochemical properties are shown in Tables 1-2.

[0066] The XRD pattern of E-3 shows peaks near 2θ = 5.1°, 8.2°, and 8.9°, indicating that catalyst E-3 is an EWT structure molecular sieve.

[0067] Preparation Example 4

[0068] Same as in Example 1, except that the structure-directing agent TDUH is replaced with TDDH (molecular formula is C). 14 H 32 N2(OH)2, MW = 262, structural formula is: (denoted as SDR, with a mass fraction of 28%). This resulted in the following molar ratios in the first mixture: SiO2 / Al2O3 = 60, Na2O / SiO2 = 0.04, SDR / SiO2 = 0.16, H2O / SiO2 = 9, ultimately yielding catalyst 4, denoted as E-4. Its physicochemical properties are shown in Tables 1-2.

[0069] The XRD pattern of E-4 shows peaks near 2θ = 5.1°, 8.2°, and 8.9°, indicating that catalyst E-4 is an EWT structure molecular sieve.

[0070] Preparation Example 5

[0071] The preparation process was the same as in Example 1, except that in step (1), the first stage of hydrothermal crystallization took 48 hours, and the second stage of hydrothermal crystallization took 96 hours. Catalyst 5, denoted as E-5, was finally obtained. Its physicochemical properties are shown in Tables 1-2.

[0072] The XRD pattern of E-5 shows peaks near 2θ = 5.1°, 8.2°, and 8.9°, indicating that catalyst E-5 is an EWT structure molecular sieve.

[0073] Preparation Example 6

[0074] The preparation method was the same as in Example 1, except that the molar ratios of the components in the first mixture were: SiO2 / Al2O3 = 60, Na2O / SiO2 = 0.04, SDR / SiO2 = 0.15, and H2O / SiO2 = 10. Specifically, 10g of solid silica gel (silicon source, calculated as SiO2), 3.176g of sodium aluminate (aluminum source, calculated as Al2O3), 23.12g of structure directing agent (TDUH, represented as SDR), and 7.378g of water were added to a Teflon liner in a liquid-to-solid order and mixed thoroughly to form the first mixture. This first mixture was then placed in a 100ml high-pressure reactor and subjected to two-stage hydrothermal crystallization in a homogeneous reactor. The final catalyst, denoted as E-6, was obtained, and its physicochemical properties are shown in Tables 1-2.

[0075] The XRD pattern of E-6 shows peaks near 2θ = 5.1°, 8.2°, and 8.9°, indicating that catalyst E-6 is an EWT structure molecular sieve.

[0076] Preparation Example 7

[0077] The preparation method is the same as in Example 1, except that in step (1), the temperature of the first stage of hydrothermal crystallization is 100℃, the temperature of the second stage of hydrothermal crystallization is 175℃, and the absolute value of the temperature difference between the first stage of hydrothermal crystallization and the second stage of hydrothermal crystallization is 75℃, and catalyst 7 is finally obtained, which is denoted as E-7. Its physicochemical properties are shown in Tables 1 to 2.

[0078] The XRD pattern of E-7 shows peaks near 2θ = 5.1°, 8.2°, and 8.9°, indicating that catalyst E-7 is an EWT structure molecular sieve.

[0079] Preparation Example 8

[0080] The preparation method is the same as in Example 1, except that in step (2), the gel molecular sieve is flocculated and mixed with a 30% ammonium chloride solution (first ammonium salt solution), and the weight ratio of the gel molecular sieve to the ammonium chloride solution is 1:50. Catalyst 8, denoted as E-8, is finally obtained. Its physicochemical properties are shown in Tables 1-2.

[0081] The XRD pattern of E-8 shows peaks near 2θ = 5.1°, 8.2°, and 8.9°, indicating that catalyst E-8 is an EWT structure molecular sieve.

[0082] Preparation Example 9

[0083] The preparation method is the same as in Example 1, except that in step (3), the solid molecular sieve is subjected to ion exchange with a 30% ammonium chloride solution (second ammonium salt solution), and the weight ratio of the solid molecular sieve to the ammonium chloride solution is 1:50. Catalyst 9, denoted as E-9, is finally obtained. Its physicochemical properties are shown in Tables 1-2.

[0084] The XRD pattern of E-9 shows peaks near 2θ = 5.1°, 8.2°, and 8.9°, indicating that catalyst E-9 is an EWT structure molecular sieve.

[0085] Preparation of Comparative Example 1

[0086] Comparative Example 1 is used to illustrate the preparation of H-ZSM-5 molecular sieves:

[0087] Nanoscale ZSM-5 molecular sieve powder (Sinopec Catalyst Company, Changling Branch) with a silicon-to-aluminum ratio of 46 was subjected to ion exchange with a 10% ammonium chloride solution. The weight ratio of ZSM-5 molecular sieve powder to ammonium chloride solution was 10, the exchange was performed 3 times, the exchange temperature was 80℃, and the time was 4h. After centrifugation 3 times until the pH value was neutral, the speed was 5000 r / min, and the time was 15min, a gel molecular sieve was obtained. The gel molecular sieve was dried in a drying oven at 120℃ for 8h, ground, and then calcined in a muffle furnace at 550℃ for 3h to obtain H-ZSM-5 molecular sieve. The molecular sieve was pressed into sheets under a pressure of 20MPa, and particles with a mesh size of 20-40 (i.e., an average particle size of 0.63-0.85mm) were screened as control catalyst 1, denoted as DZ-1. Its physicochemical properties are shown in Tables 1-2.

[0088] Preparation of Comparative Example 2

[0089] The preparation was the same as that of Comparative Example 1, except that the nano-sized ZSM-5 molecular sieve powder with a silicon-to-aluminum ratio of 46 was replaced with the same amount of micron-sized ZSM-5 molecular sieve powder with a silicon-to-aluminum ratio of 38 (Nankai University Catalyst Factory). The final result was Comparative Catalyst 2, denoted as DZ-2, and its physicochemical properties are shown in Tables 1-2.

[0090] Preparation of Comparative Example 3

[0091] Comparative Example 3 is used to illustrate the preparation of H-MOR molecular sieves:

[0092] The preparation method was the same as Comparative Example 1, except that the nano-sized ZSM-5 molecular sieve powder with a silica-to-alumina ratio of 46 was replaced with the same amount of MOR molecular sieve powder with a silica-to-alumina ratio of 20 (Sinopec Petrochemical Research Institute Co., Ltd.), ultimately yielding H-MOR molecular sieve. This molecular sieve was pressed into sheets under 20 MPa pressure, and particles of 20–40 mesh (i.e., average particle size of 0.63–0.85 mm) were screened as comparative catalyst 3, denoted as DM-1. Its physicochemical properties are shown in Tables 1–2, and the nitrogen isotherm curve is shown in... Figure 3 As shown, Figure 3 It can be seen that DM-1 has a low mesoporous content.

[0093] Preparation of Comparative Example 4

[0094] Same as in Example 1, except that in step (1), the temperature of the first stage of hydrothermal crystallization is 120°C and the time is 144h, and the second stage of hydrothermal crystallization is not performed. Finally, comparative catalyst 4 is obtained, denoted as DE-1, and its physicochemical properties are shown in Tables 1 to 2.

[0095] The XRD pattern of DE-1 shows peaks near 2θ = 6.6° and 7.3°, indicating that DE-1 is an MCM-22 molecular sieve with a large number of impurities.

[0096] Table 1

[0097]

[0098]

[0099] Table 2

[0100]

[0101] As can be seen from the data in Tables 1 and 2 above, the EWT structured molecular sieve provided in this disclosure has an ultra-large channel structure composed of 21MR and 10MR channels, which gives the molecular sieve an ultra-large specific surface area, a large total pore volume and mesopore volume, and a lamellar morphology. When used for the gas-phase non-hydroisomerization synthesis of mesitylene from pseudotrimethylbenzene, it is beneficial to improve the isomerization reaction rate and product diffusion rate, thereby improving the catalytic activity and stability of the molecular sieve and extending the service life of the catalyst.

[0102] The following examples and comparative examples illustrate the methods for catalyzing the gas-phase non-hydroisomerization reaction of pseudotrimethylbenzene using different catalysts.

[0103] Example 1

[0104] 2g of E-1 was packed into a fixed-bed reactor, and pseudotrimethylbenzene was added as a reactant. The reaction conditions were: reaction temperature 300℃, reaction pressure 0.1MPa, nitrogen flow rate 16mL / min, and pseudotrimethylbenzene mass hourly space velocity 0.5h⁻¹. -1 Online GC analysis of all components. The conversion rate, selectivity and yield of mesitylene at reaction times of 30 h and 90 h are shown in Table 3, and were calculated according to the methods shown in equations (1) to (3) below:

[0105]

[0106]

[0107] Mestriylene mass yield = metatriylene conversion × mestriylene selectivity × 100% Equation (3).

[0108] Examples 2-9

[0109] The isomerization reaction of tricresyl was carried out according to the method and reaction conditions of Example 1, and the isomerization reaction was catalyzed by the catalysts prepared in Examples 2-9. The reaction results are shown in Table 3.

[0110] Comparative Examples 1-4

[0111] The isomerization reaction of tricresyl was carried out according to the method and reaction conditions of Example 1. The comparative catalysts prepared in Comparative Examples 1-4 were used to catalyze the isomerization reaction. The reaction results are shown in Table 3.

[0112] Table 3

[0113]

[0114]

[0115] From Table 3 above and Figure 4 The results show that the EWT molecular sieve with a suitable pore structure, used in this disclosure as a catalyst, can improve the conversion rate, selectivity, and mass yield of pseudotrimethylbenzene in the gas-phase non-hydroisomerization reaction of pseudotrimethylbenzene, slow down the carbon deposition of heavy components, and extend the catalyst's lifespan. Even after 90 hours of continuous reaction, the catalyst still maintains a high yield of mesitylene, with the mass yield remaining above 20% without significant decline. Comparative Examples 1-4 did not use the implementation method of this disclosure. Comparative Examples 1-2 used ZSM-5 molecular sieves, resulting in lower conversion rates or selectivity for pseudotrimethylbenzene, and a significant decrease in the mass yield of mesitylene after 90 hours of continuous reaction, dropping to around 5-7%, making long-term operation unsuitable. Comparative Example 3 used MOR molecular sieves as a catalyst; the high-temperature aerobic weight loss curve after 90 hours of catalytic pseudotrimethylbenzene gas-phase non-hydroisomerization reaction is shown in the figure below. Figure 4 As shown, Figure 4 It can be seen that as the temperature increases, the mass of the MOR molecular sieve decreases sharply by 9.6%, indicating that the MOR molecular sieve has poor thermal stability and is prone to decomposition; while under the same conditions, the mass loss of catalyst 1 is only 4.2%, indicating that catalyst 1 has better thermal stability. The molecular sieve synthesized in Comparative Example 4 without two-stage crystallization has more impurities and the yield of mesitylene is extremely low.

[0116] The preferred embodiments of this disclosure have been described in detail above with reference to the accompanying drawings. However, this disclosure is not limited to the specific details of the above embodiments. Within the scope of the technical concept of this disclosure, various simple modifications can be made to the technical solutions of this disclosure, and these simple modifications all fall within the protection scope of this disclosure.

[0117] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, this disclosure will not describe the various possible combinations separately.

[0118] Furthermore, various different embodiments of this disclosure can be combined in any way, as long as they do not violate the spirit of this disclosure, they should also be regarded as the content disclosed in this disclosure.

Claims

1. A method for synthesizing mesitylene by gas-phase non-hydroisomerization of pseudotrimethylbenzene, characterized in that, The method includes contacting p-trimethylbenzene with a catalyst under gas-phase non-hydroisomerization reaction conditions and in the presence of a catalyst; wherein the catalyst is an EWT-structured molecular sieve with a total pore volume of 0.20–0.51 cm³. 3 ·g -1 The mesopore volume is 0.11–0.37 cm³. 3 ·g -1 .

2. The method according to claim 1, characterized in that, The conditions for the gas-phase non-hydroisomerization reaction include: contacting the catalyst with p-xylene under a nitrogen atmosphere, wherein the nitrogen flow rate is 5–50 mL / min, preferably 10–30 mL / min; the contact temperature is 240–400 °C, preferably 280–360 °C; the contact time is 10–60 h, preferably 20–45 h; and the pressure is 0.1–1.2 MPa, preferably 0.1–0.5 MPa. Preferably, the reaction is carried out in a fixed-bed reactor, and the mass hourly space velocity (WHSV) of the pseudotrimethylbenzene is 0.5–1.0 h⁻¹. -1 .

3. The method according to claim 1, characterized in that, The total pore volume of the EWT structured molecular sieve is 0.28–0.46 cm³. 3 ·g -1 The mesopore volume is 0.15–0.35 cm³. 3 ·g -1 The total specific surface area is 500-600 m². 2 ·g -1 Preferably, it is 520-550m 2 g -1 .

4. The method according to claim 1, characterized in that, The EWT structured molecular sieve, as determined by the NH3-TPD method, has a medium-strong acid content accounting for 40-65% of the total acid content, preferably 60-65%; the ratio of Brønsted acid to Lewis acid, as determined by pyridine adsorption infrared spectroscopy at 200℃, is 0.5-2, preferably 1-2; and the ratio of Brønsted acid to Lewis acid, as determined by pyridine adsorption infrared spectroscopy at 350℃, is 0.1-0.4, preferably 0.15-0.

4. Preferably, the total acidity of the EWT structured molecular sieve, as measured by the NH3-TPD method, is 420–600 μmol / g, and more preferably 550–600 μmol / g.

5. The method according to claim 1, characterized in that, The molar ratio of silicon (calculated as SiO2) to aluminum (calculated as Al2O3) in the EWT structured molecular sieve is 60–120, preferably 60–90; the EWT structured molecular sieve has a layered structure and is an H-EWT molecular sieve.

6. The method according to claim 1, characterized in that, The method further includes preparing the EWT structured molecular sieve using the following steps: (1) A silicon source, an aluminum source, an alkali source, a structure-directing agent, water, and an optional mineralizer are mixed to obtain a first mixture; the first mixture is subjected to a first stage of hydrothermal crystallization and a second stage of hydrothermal crystallization to obtain a gel molecular sieve; wherein the temperature of the first stage of hydrothermal crystallization is lower than the temperature of the second stage of hydrothermal crystallization. (2) The gel molecular sieve is flocculated and mixed with the first ammonium salt solution, and the resulting second mixture is subjected to first drying and first calcination to obtain a solid molecular sieve; (3) The solid molecular sieve is brought into contact with the second ammonium salt solution for ion exchange, and then subjected to second drying and second calcination.

7. The method according to claim 6, characterized in that, In step (1), the silicon source is SiO2, the aluminum source is Al2O3, the alkali source is alkali metal oxide M2O, and the structure directing agent is SDR. In the first mixture, the molar ratio of SiO2 to Al2O3 is 60-180, preferably 60-120; the molar ratio of M2O to SiO2 is 0.01-0.2, preferably 0.04-0.18; the molar ratio of SDR to SiO2 is 0.06-0.18, preferably 0.10-0.16; the molar ratio of water to SiO2 is 8-20, preferably 9-15; and the molar ratio of mineralizer to SiO2 is 0-0.1, preferably 0-0.

05. The absolute value of the temperature difference between the first stage of hydrothermal crystallization and the second stage of hydrothermal crystallization is 15-55℃, preferably 20-40℃; more preferably, the temperature of the first stage of hydrothermal crystallization is 100-160℃, preferably 120-140℃, and the time is 12-48h, preferably 24-48h; the temperature of the second stage of hydrothermal crystallization is 150-180℃, preferably 160-180℃, and the time is 96-132h, preferably 96-120h.

8. The method according to claim 6, characterized in that, In step (1), the silicon source is selected from one or more of solid silica gel, silica sol, tetraethyl orthosilicate and fumed silica, preferably solid silica gel; The aluminum source is selected from one or more of sodium aluminate, aluminum trichloride, aluminum sulfate and aluminum sol, preferably sodium aluminate; The alkali source is selected from one or more of sodium hydroxide, potassium hydroxide, sodium oxide and potassium oxide, preferably sodium hydroxide; The structure-directing agent is selected from at least one having the structure shown in formula (1): R1 to R4 are each independently selected from alkyl groups having 1 to 4 carbon atoms. Preferably, R1 to R4 are each independently selected from one or more of methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, and tert-butyl, preferably methyl or ethyl; m is 2 or 3; n is any integer from 1 to 10; X - This includes hydroxide ions or halide anions.

9. The method according to claim 6, characterized in that, In step (2), the weight ratio of the gel molecular sieve to the first ammonium salt solution is 1:(10-50), preferably 1:(10-30); the temperature of the first drying is 80-150℃, preferably 100-120℃; the time is 8-12h, preferably 8-10h; the temperature of the first calcination is 400-600℃, preferably 450-550℃; the time is 2-6h, preferably 3-5h. The concentration of the first ammonium salt solution is 10-30% by weight, and the first ammonium salt solution is selected from one or more of ammonium chloride solution, ammonium nitrate solution and ammonium sulfate solution.

10. The method according to claim 6, characterized in that, In step (3), the weight ratio of the solid molecular sieve to the second ammonium salt solution is 1:(10-40), preferably 1:(20-30); the ion exchange temperature is 60-100℃, preferably 65-80℃; the time is 2-8h, preferably 4-8h; the second drying temperature is 80-150℃, preferably 80-120℃; the time is 8-12h, preferably 8-10h; the second calcination temperature is 400-600℃, preferably 450-550℃; the time is 2-6h, preferably 3-5h. The concentration of the second ammonium salt solution is 10-30% by weight, and the second ammonium salt solution is selected from one or more of ammonium chloride solution, ammonium nitrate solution and ammonium sulfate solution.

Citation Information

Patent Citations

  • Preparation method and application of catalyst for catalyzing unsym-trimethylbenzene to produce mesitylene

    CN116786158A

Cited By

  • Preparation method of catalyst for preparing mesitylene by isomerization of unsym-trimethylbenzene

    CN122298483A